Does Board Education Diversity Affect Environmental Accounting Disclosure? Evidence from Listed Firms in Kenya - Kipngetich, Tarus John; Bonuke, Ronald; Tenai, Joel (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose- The purpose of this study was to examine the effect of board education diversity on environmental accounting disclosure among firms listed in the Nairobi Security Exchange. Design/Methodology- The study adopted both explanatory and longitudinal research design. The target population comprised 65 listed firms at Nairobi Securities Exchange from 2008 to 2017. However, inclusion criteria were the 27 listed firms from 2008 to 2017, giving a total of 270 observations. A documentary analysis guide was used to collect secondary data. Findings- The findings showed that board education had a significant and positive impact on environmental accounting disclosure. The findings validate the human capital theory's proposition. Practical Implications- Firms listed at the Nairobi Securities Exchange ought to diffuse the education level of the board of directors to increase the level of environmental accounting disclosure. Besides, their boards should be well educated and experienced to enhance disclosure of environmental accounting.